Chlorine analysis on palm olein - Jasni, Mohamad Iman Benji (2019)
In In palm oil industry, during the deodorization stage of the edible oils, chlorine ion is said to be formed as high temperature of the treatment caused the ion to bond to the hydrocarbon chain of the lipid molecule in oil. The chloride formation is categorized as contaminants by the European Food Safety Authority (EPSA) which they focused on 3-monochloropropane-1,2-diol (3-MCPD) compound. In certain studies, the formation of chloride ion could cause a harmful effect towards health. Thus, this research focuses to determine the total chlorine content in palm oil. For this research, palm olein is chosen as sample and it was analyzed through few methods to determine its total chlorine content. The methods are classified into two types and each analysis involves two kinds of testing methods. The results obtained in the wet chemical analysis is interpreted in standard deviation and average value that was obtained. Among the samples prepared, it can be observed that wet chemical analysis shows consistency results of chlorine content compared to instrumental chemical analysis.